TINGKAT PEMAHAMAN MASYARAKAT TERHADAP PEMILAHAN SAMPAH RUMAH TANGGA DI DESA PADEMARE LOMBOK UTARA - Lolom Evalita Hutabarat; Candra Christianti Purnomo (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2021)
The problem of household waste often causes environmental pollution. Lack of education to the public about the impact of waste makes residents often underestimate it. The socialization of household waste management by sorting waste with the 3R principle (Reduce, Reuse, Recycle) has been campaigned since 2006. To measure the level of community understanding of this, research was conducted through questionnaires to the community in Pade Mare in Sambik Elen Village, North Lombok. Data analysis is presented in the form of descriptive statistics from the results of a questionnaire consisting of 24 question instruments with 3 indicators, namely waste reduction, waste recycling, and waste processing. The survey results show that the level of community understanding about waste reduction, waste recycling, and waste processing is good with an average score of 76.76; 76.67, and 79.03 respectively. The higher average value of waste processing is in line with the location of the Pade Mare which has many farms so that the processing of animal waste is quite often carried out by the local community. Understanding the importance of sorting waste does not automatically make people take action to sort waste because 91% of respondents still combine all the waste to be disposed of without sorting it out first. For this reason, periodic socialization to the community is needed